Macroeconomic Risk and Debt Overhang* - Chen, Hui; Manso, Gustavo (The Review of Corporate Finance Studies, 2017)
– Since corporate debt tends to be riskier in recessions, transfers from equity holders to debt holders that accompany corporate decisions also tend to concentrate in recessions. Such systematic risk exposures of debt overhang have important implications for corporate investment and financing decisions, and for the ex ante costs of debt overhang. Using a calibrated dynamic capital structure model, we show that the costs of debt overhang become higher in the presence of macroeconomic risk. We also provide several new predictions on how the cyclicality of a firm’s assets in place and growth options affect its investment and capital structure decisions.